La formalización del microempresario del servicio público de transportes de pasajeros (modalidad de microbuses) y su contribución en la dinamización de la economía en la Provincia de Trujillo - Benites Requena, Carlos Iván (2018)
The development of this research work entitled "The formalization of the micro entrepreneur of the public passenger transport service and its contribution to the revitalization of the economy in the province of Trujillo", has as its general objective to determine the contribution of the formalization of the micro businessman of the public service of passenger transport in the revitalization of the economy of said city, establishing the degree of labor-tax informality and suggesting specific recommendations. With the investigation, the informality of the micro entrepreneurs of the public transport service of passengers was evaluated, to then develop the pertinent steps that comprise the scientific research methodology. The results show that the factors that associate informality with micro entrepreneurs are the outsourcing of the transport route, the illegal treatment of the owner of the minibus and its workers (driver and collector) and the omission of their income. It shows that the formalization contributes positively, since its application means great labor benefits for its workers and higher tax collection for the state which would generate a better dynamism of the economy in the city. However, it is demonstrated that the lack of attention from the local government and central government towards the public transport companies continue not to declare all their net income, thus maintaining a no better income and lower living conditions.